TINJAUAN TENTANG KEWAJIBAN PELAPORAN TRANSAKSI KEUANGAN OLEH ADVOKAT DALAM KETENTUAN UNDANG-UNDANG NO. 18 TAHUN 2003 TENTANG ADVOKAT YANG TIDAK SEJALAN DENGAN PERATURAN PEMERINTAH NOMOR 43 TAHUN 2015 TENTANG PIHAK PELAPOR DALAM PEMBERANTASAN DAN PENCEGAHAN TINDAK PIDANA PENCUCIAN UANG - Narada Lukman; Tatang Ruchimat (Fakultas Hukum Universitas Tarumanagara, 2019)
The legal norms of any country are always multi-layered, where the norms below apply, are based on and come from higher norms, higher norms apply, are based and are sourced from even higher norms, up to a norm the highest is called the Basic Norm. Since the birth Republic of Indonesia with proclamation independence, as well as the adoption from the 1945 Constitution as the constitution the Indonesian State, the proof legal norm system the Republic of Indonesia, If we compare it with the theory of the level of legal norms (Stufen Theory) from Hans Kelsen and the theory of the level of legal norms, that Article 3 letter a of Government Regulation No. 43 of 2015 adheres to the Advocate Law No. 18 of 2003. Article 3 letter a Government Regulation reads